Jasmonates alleviate spikelet‐opening impairment caused by high temperature stress during anthesis of photo‐thermo‐sensitive genic male sterile rice lines. (14th July 2020) - Yang, Jianchang; Fei, Keqi; Chen, Jing; Wang, Zhiqin; Zhang, Weiyang; Zhang, Jianhua
Abstract: Hybrids produced by photo‐thermo‐sensitive genic male sterile (PTSGMS) rice ( Oryza sativa L.) lines crossed with restorer lines have huge heterosis. However, PTSGMS rice lines show serious spikelet‐opening impairment as high temperature (HT) stress occurs during anthesis. Its physiological mechanism remains unclear. Jasmonates (JAs) are novel phytohormones and play important roles in responses to biotic and abiotic stresses. This study investigated whether and how JAs mediate the effect of HT stress during anthesis on spikelet‐opening of PTSGMS rice lines. Three PTSGMS rice lines were pot‐grown and subjected to HT stress during anthesis. The concentrations of jasmonic acid (JA), methyl jasmonate (MeJA), hydrogen peroxide (H2 O2 ), ascorbic acid (AsA), and soluble sugars and activities of catalase and α‐amylase in the lodicules that locate at the base inside the lemma and function spikelet‐opening were determined. The results showed that increases or decreases in JA and MeJA concentrations in the lodicules under HT stress varied with PTSGMS lines. A PTSGMS line with higher JA and MeJA concentrations under HT stress exhibited a higher opened‐spikelet rate and also showed a higher fertilized‐spikelet rate and a higher seed yield when the line was crossed with a restorer line. Both JA and MeJA concentrations were very significantly ( p = .01) and positively correlated with AsA concentrations and activities of catalase and α‐amylase, whereas were negatively correlated with H2 O2 concentration. Increases in concentrations of JAs in lodicules by applying JA or MeJA under HT stress during anthesis significantly increased activities of catalase and α‐amylase and concentrations of AsA and soluble sugars, and significantly decreased H2 O2 concentration in the lodicules, and, accordingly, increased opened‐spikelet rate. The results suggest that JAs play an important role in alleviating spikelet‐opening impairment caused by HT stress during anthesis through enhancing antioxidant ability and osmotic regulation in the lodicules of PTSGMS rice lines. Abstract : Increases or decreases in the concentrations of jasmonic acid (JA) and methyl jasmonate (MeJA) in the lodicules under high temperature (HT) stress varied with photo‐thermo‐sensitive genic male sterile (PTSGMS) rice lines.